Innovation Capability Models to Improve the Competitiveness of Creative Industrial Products - Farida, Naili; Pradhanawati, Ari; Taufiq, Mochamad (JURNAL ILMU SOSIAL, 2021)
This study aims to build a model of innovation capability to increase the competitiveness of embroidery products in Jepara. The respondents in this study were 132 owners of embroidery SMEs. The sampling technique used was purposive sampling and the analysis technique employed Partial Least Square (PLS). Research results show a variety of knowledge, i.e., customer orientation has significant positive effect on innovation capability. Customer orientation and innovation capability significantly affect marketing performance, but competitive finance has no significant effect on marketing performance. In addition, the competitiveness of embroidery products is still low, so there is no impact on marketing performance. The competitive advantage of the product must be unique to the competitors’ embroidery products that have not been able to improve the competitiveness of their embroidery products.